A Debreceni Nyári Egyetem újraindításának körülményei 1947-ben - Varga, Mátyás (Gerundium, 2015)
THE RESTART OF THE DEBRECEN SUMMER SCHOOL IN 1947. he essay recalls the process of restarting the Debrecen Summer School after WWII, which operated continously even during the war, and the history of the irst courses organized on the basis of the previous structure. he author describes in detail the heroic struggle of numerous professors in Debrecen, primarily János Hankiss, aiming at reviving the Summer School and putting together the necessary funds for it. he essay elaborates on the obstructive factors and barriers rising immediately after the war and contributing to the complete disintegration of the school.